2013
DOI: 10.2105/ajph.2013.301312
|View full text |Cite
|
Sign up to set email alerts
|

Housing Retention in Single-Site Housing First for Chronically Homeless Individuals With Severe Alcohol Problems

Abstract: Objectives We studied housing retention and its predictors in the single-site Housing First model. Methods Participants (n = 111) were chronically homeless people with severe alcohol problems who lived in a single-site Housing First program and participated in a larger nonrandomized controlled trial (2005–2008) conducted in Seattle, Washington. At baseline, participants responded to self-report questionnaires assessing demographic, illness burden, alcohol and other drug use, and psychiatric variables. Housin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
88
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 29 publications
2
88
0
1
Order By: Relevance
“…The former finding is consistent with prior studies that have found older HF tenants to have higher rates of housing retention, [11][12][13][14] and may reflect lower levels of substance abuse among older adults, which has been linked to housing failure in prior studies of HF. 11,15 The latter finding may reflect that individuals who have the highest needs and are hardest to place in an initial housing unit continue to experience substantial barriers to housing stability even after they move in to housing.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The former finding is consistent with prior studies that have found older HF tenants to have higher rates of housing retention, [11][12][13][14] and may reflect lower levels of substance abuse among older adults, which has been linked to housing failure in prior studies of HF. 11,15 The latter finding may reflect that individuals who have the highest needs and are hardest to place in an initial housing unit continue to experience substantial barriers to housing stability even after they move in to housing.…”
supporting
confidence: 88%
“…Aubry et al 6 considered housing stability to be "defined as living in one's own room, apartment, or house or with family for an expected duration of at least six months or having tenancy rights (holding a lease to the housing)." Collins et al 7 measured both whether a person maintained residency during the 2 years after they moved into a specific HF project building and "the number of days they spent continuously housed during the 2 years." Yet, as Pearson et al 8 explained, housing stability is "an iterative process" that may include loss of housing and changes in residential address.…”
Section: Introductionmentioning
confidence: 99%
“…Dados nacionais apontam que 35,5% da população em situação de rua do país referem o uso abusivo de álcool ou de outras drogas como a principal motivação para passar a viver e morar na rua, e 28% informam já ter passado por alguma casa ou clínica de recuperação para dependentes químicos 23 . Estudos internacionais com populações em situação de rua apontam que esses indivíduos identificam o uso de substâncias como uma das principais razões para sua perda de moradia e permanência na rua 24 . Da mesma forma, pessoas que dependem de programas de moradia, ou que não têm moradia estável, apresentam maior índice de abuso e/ou dependência de substâncias ilícitas, o que pode levar ao envolvimento com a justiça criminal e gerar relações tensas com familiares e amigos, afetando, ainda mais, sua capacidade de garantir a habitação 25 .…”
Section: Tabelaunclassified
“…Permanent supportive housing has been credited with decreasing chronic homelessness by 25% from 2006 to 2013 through federal funding initiatives such as Shelter Plus Care and through local and state investment (8-10). However, substantial variation exists in the implementation of permanent supportive housing (11,12). Although there are well-articulated models for it (13), the definition of permanent supportive housing beyond the notion of providing permanent housing with ongoing supportive services remains underspecified (14).…”
mentioning
confidence: 99%